A Theoretical Analysis for Money Demand and Money Market Equilibrium in Libya (Journal of human and social sciences, 2026)
The building visual model was the main aim of this study that based on the Keynesian theory and the subsequent developments of demand for money, the visual model of the study adopted some hypotheses for money supply function that was mentioned in a previous study by Ben Taher (2021), the study is considered as first attempt for obtaining visual model has ability to explain the Libyan money market and interpret the effect of some economic policies conducted recently by the Libyan authorities. The descriptive analysis method, mathematical equations and figures were used to examine four principle hypotheses proving the inability of the traditional formula to explain the economic variables affecting the Libyan money market. The main results of the theoretical investigation showed that the required amount of the Libyan dinar is changed positively with public expenditure and inversely with the exchange rate of the Libyan dinar in the black market. The study results were deferent of recent previous study conducted by Ben Taher (2021), where found that the change in the quantity of money supply depends on the Central Bank of Libya (CBL) decisions to print more banknotes to meet money demand surplus and also depends on the legislative authority’s decisions to authorize CBL to lend the government for funding the public budget deficit. The results also found that there is an inverse relationship between the lack of liquidity and the exchange rate of the Libyan dinar in the black market.
Keywords: Monetary Equilibrium; Monetary Policy; Public Expenditure; Liquidity; Central Bank of Libya (CBL)